Smart cyber physical systems : advances, challenges and opportunities - Karpagam, G. R.; Kumar, B. Vinoth; Maheswari, J. Uma; Gao, Xiao-Zhi, 1972- (Boca Raton, FL : CRC Press, 2021)
Smart Cyber Physical Systems: Advances, Challenges and Opportunities ISBN: 9780367337889 Cyber Physical Systems (CPS) are the new generation of collaborative computational entities, with a prime focus on integration of the physical world and cyber space. Through a feedback mechanism, the system adapts itself to new conditions in real time. The scope of this book includes research experience by experts in CPS infrastructure systems, incorporating sustainability by embedding computing and communication in day-to-day applications. CPS, integrated with Blockchain, Artificial Intelligence, Internet of Things, Big Data, Cloud Computing and Communication, lay a foundation for the fourth industrial revolution, Industry 4.0. This book will be of immense use to practitioners in industries with a focus on autonomous and adaptive configuration, and on optimization, leading to increased agility, elasticity and cost effectiveness. The contributors of this book include renowned academics, industry practitioners and researchers. It offers a rigorous introduction to the theoretical foundations, techniques and practical solutions, through case studies. Building CPS with effective communication, control, intelligence and security is discussed in terms of societal and research perspectives. The objective of this book is to provide a forum for researchers and practitioners to exchange ideas and to achieve progress in CPS by highlighting applications, advances and research challenges. It is highly recommended to be used as a reference book for graduate and post-graduate level programmes in universities, with a focus on research in computer science-related courses.
Building Cyber Physical Systems -- Design Challenges, Techniques. SWOT Analysis of Cyber Physical Systems (CPS). Building Cyber physical Systems -- Context -- Wireless Sensor Networks. Intelligent Building and Environmental Controls for Futuristic Smart Cities Powered by Cyber Physical Intelligence. Smart Agriculture: An Application of Cyber Physical Systems. Building Cyber Physical Systems in the context of Smart Cities. Cyber Physical Systems for Disaster Response Networks: Conceptual Proposal using Never Ceasing Network. Risk-Adjusted Supply Chain Execution in the Era of Digital Supply Chains. War Gaming for Cyber Physical Systems. Blockchain Enabled Cyber Physical System -- Case Study: SmartGym. Context-Aware Computing For Cyber Physical Systems. Intelligent Social Networking in Cyber Physical Systems. Manufacturing in Future as a Cyber Physical System. Cyber Physical Systems Threat Landscape. Proactive UDDI for retrieval of Superior Web Services predominantly for Cyber Physical Systems.
"A Chapman & Hall book."
OCLC-licensed vendor bibliographic record.
Keywords: Cooperating objects (Computer systems); COMPUTERS / General; COMPUTERS / Computer Engineering; COMPUTERS / Computer Science